An Analysis of Prose as a Medium of Protest and Social Change - Nonis (Politeknik Siber Cerdika Internasional, 2024)
This study examines prose as a potent medium for social criticism, analysing how literary works convey protest and advocate for social change. By delving into prose that critiques prevailing social structures, policies, or dominant values whether explicitly or through subtle narratives this research seeks to uncover the ways in which literature can serve as a catalyst for awareness and transformation. Through close readings and thematic analysis, the study highlights the narratives and stylistic elements that allow prose to confront societal injustices, mobilize empathy, and inspire readers toward progressive thought and action. The impact of such literature extends beyond entertainment, as it sensitizes audiences to critical social issues, empowering them with a reflective lens on their own societal contexts. This exploration of prose as a vehicle for protest underscores the enduring power of storytelling in challenging the status quo and advocating for a more equitable society.